Who-ology : Doctor Who : the official miscellany - Scott, Cavan; Wright, Mark. (London : BBC Books, 2013)
Do you know your Sontarans from your Silurians? What are the 40 best ways to defeat a Dalek? What are the galactic coordinates of Gallifrey? This title deals with these questions.
Keywords: Doctor Who (Television program : 2005- ); Science fiction television programs -- Great Britain